{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

MS-Sol-EE-C02

# MS-Sol-EE-C02 - CHAPTER 2 THE BINOMIAL EXPANSION EXERCISE...

This preview shows pages 1–4. Sign up to view the full content.

CHAPTER 2 THE BINOMIAL EXPANSION EXERCISE 2.1 Section 2.1 The binomial theorem (page 33) 1. ( a + b ) 3 = a 3 + 3 a 2 b + 3 ab 2 + b 3 2. (1 + x ) 7 = 1 + 7 x + 21 x 2 + 35 x 3 + 35 x 4 + 21 x 5 + 7 x 6 + x 7 3. ( a + b ) 8 = a 8 + 8 a 7 b + 28 a 6 b 2 + 56 a 5 b 3 + 70 a 4 b 4 + 56 a 3 b 5 + 28 a 2 b 6 + 8 ab 7 + b 8 4. (1 + x ) 9 = 1 + 9 x + 36 x 2 + 84 x 3 + 126 x 4 + 126 x 5 + 84 x 6 + 36 x 7 + 9 x 8 + x 9 5. (1 + 2 x ) 2 = 1 + 2(2 x ) + (2 x ) 2 = 1 + 4 x + 4 x 2 6. (1 + 6 x ) 3 = 1 + 3(6 x ) + 3(6 x ) 2 + (6 x ) 3 = 1 + 18 x + 108 x 2 + 216 x 3 7. (1 - 4 x ) 4 = 1 - 4(4 x ) + 6(4 x ) 2 - 4(4 x ) 3 + (4 x ) 4 = 1 - 16 x + 96 x 2 - 256 x 3 + 256 x 4 8. (2 x + y ) 5 = (2 x ) 5 + 5(2 x ) 4 y + 10(2 x ) 3 y 2 + 10(2 x ) 2 y 3 + 5(2 x ) y 4 + y 5 = 32 x 5 + 80 x 4 y + 80 x 3 y 2 + 40 x 2 y 3 + 10 xy 4 + y 5 9. ( a + 3 b ) 6 = a 6 + 6 a 5 (3 b ) + 15 a 4 (3 b ) 2 + 20 a 3 (3 b ) 3 + 15 a 2 (3 b ) 4 + 6 a (3 b ) 5 + (3 b ) 6 = a 6 + 18 a 5 b + 135 a 4 b 2 + 540 a 3 b 3 + 1 215 a 2 b 4 + 1 458 ab 5 + 729 b 6 10. (1 - 2 x 2 ) 7 = 1 - 7(2 x 2 ) + 21(2 x 2 ) 2 - 35(2 x 2 ) 3 + 35(2 x 2 ) 4 - 21(2 x 2 ) 5 + 7(2 x 2 ) 6 - (2 x 2 ) 7 = 1 - 14 x 2 + 84 x 4 - 280 x 6 + 560 x 8 - 672 x 10 + 448 x 12 - 128 x 14 11. 5 1 - x x = 5 4 3 2 2 3 4 5 1 1 5 + 1 10 1 10 + 1 5 - - - x x x x x x x x x x = 5 3 3 5 1 5 + 10 10 + 5 x x x x x x - - - 12. 4 2 1 + x x = x 4 + 4 x 3 2 1 x + 6 x 2 2 2 1 x + 4 x 3 2 1 x + 4 2 1 x = x 4 + 4 x + 2 6 x + 5 4 x + 8 1 x 13. (1 + 3 x ) 10 = 1 + 3 10 3 2 10 2 10 1 ) 3 ( + ) 3 ( + ) 3 ( x C x C x C + . . . = 1 + 30 x + 405 x 2 + 3 240 x 3 + . . . 14. (1 - 2 x ) 17 = 1 - C 17 1 (2 x ) + C 17 2 (2 x ) 2 - C 17 3 (2 x ) 3 + . . . = 1 - 34 x + 544 x 2 - 5 440 x 3 + . . . 15

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
C HAPTER 2 T HE B INOMIAL E XPANSION 15. (2 - x ) 9 = 3 6 9 3 2 7 9 2 8 9 1 9 ) 2 ( ) 2 ( + ) 2 ( 2 x C x C x C - - + . . . = 512 - 2 304 x + 4 608 x 2 - 5 376 x 3 + . . . 16. (3 + x ) 11 = 3 11 + C 11 1 (3 10 ) x + C 11 2 (3 9 ) x 2 + C 11 3 (3 8 ) x 3 + . . . = 177 147 + 649 539 x + 1 082 565 x 2 + 1 082 565 x 3 + . . . 17. (1 + x ) 6 (1 - x ) 4 = (1 + 6 x + 15 x 2 + 20 x 3 + . . . ) (1 - 4 x + 6 x 2 - 4 x 3 + x 4 ) = 1 + 2 x - 3 x 2 - 8 x 3 + . . . 18. (1 + 3 x ) 2 (1 + x ) 5 = [1 + 2(3 x ) + (3 x ) 2 ] (1 + 5 x + 10 x 2 + 10 x 3 + . . .) = (1 + 6 x + 9 x 2 ) (1 + 5 x + 10 x 2 + 10 x 3 + . . .) = 1 + 11 x + 49 x 2 + 115 x 3 + . . . 19. (3 + x ) 5 (2 + 7 x ) 7 = [3 5 + 5(3 4 ) x + 10(3 3 ) x 2 + 10(3 2 ) x 3 + . . .] [2 7 + 7(2 6 ) (7 x ) + 21(2 5 ) (7 x ) 2 + 35(2 4 ) (7 x ) 3 + . . . ] = [243 + 405 x + 270 x 2 + 90 x 3 + . . . ] [128 + 3 136 x + 32 928 x 2 + 192 080 x 3 + . . . ] = 31 104 + 813 888 x + 9 306 144 x 2 + 60 869 520 x 3 + . . . 20. (2 - x ) 3 (5 + x ) 4 = [2 3 - 3(2 2 ) x + 3(2) x 2 - x 3 ] [5 4 + 4(5 3 ) x + 6(5 2 ) x 2 + 4(5) x 3 + x 4 ] = (8 - 12 x + 6 x 2 - x 3 ) (625 + 500 x + 150 x 2 + 20 x 3 + x 4 ) = 5 000 - 3 500 x - 1 050 x 2 + 735 x 3 + . . . 21. (1 + x - 2 x 2 ) 5 = [1 + x (1 - 2 x )] 5 = 1 + 5 x (1 - 2 x ) + 10 x 2 (1 - 2 x ) 2 + 10 x 3 (1 - 2 x ) 3 + . . . = 1 + 5 x - 10 x 2 + 10 x 2 (1 - 4 x + 4 x 2 ) + 10 x 3 + . . . = 1 + 5 x - 30 x 3 + . . . 22. (1 + 3 x + x 2 ) 8 = [1 + x (3 + x )] 8 = 1 + 8 x (3 + x ) + 28 x 2 (3 + x ) 2 + 56 x 3 (3 + x ) 3 + . . . = 1 + 24 x + 8 x 2 + 28 x 2 (9 + 6 x + x 2 ) + 1 512 x 3 + . . . = 1 + 24 x + 260 x 2 + 1 680 x 3 + . . . 23. (1 - 4 x - 3 x 2 ) 12 = [1 - x (4 + 3 x )] 12 = 1 - 12 x (4 + 3 x ) + 66 x 2 (4 + 3 x ) 2 - 220 x 3 (4 + 3 x ) 3 + . . . = 1 - 48 x - 36 x 2 + 66 x 2 (16 + 24 x + 9 x 2 ) - 14 080 x 3 + . . . = 1 - 48 x + 1 020 x 2 - 12 496 x 3 + . . . 24. (1 - x + 5 x 2 ) 11 = [1 - x (1 - 5 x )] 11 = 1 - 11 x (1 - 5 x ) + 55 x 2 (1 - 5 x ) 2 - 165 x 3 (1 - 5 x ) 3 + . . . = 1 - 11 x + 55 x 2 + 55 x 2 (1 - 10 x + 25 x 2 ) - 165 x 3 + . . . = 1 - 11 x + 110 x 2 - 715 x 3 + . . . 25. The ( r + 1)th term = C x x r r r 9 9 2 2 3 ( ) - - = C x r r r r 9 9 9 3 2 3 ( ) ( ) - - - If the term is independent of x , then 9 - 3 r = 0 r = 3 The term independent of x = C 3 9 9 3 3 2 3 ( ) ( ) - - = - 145 152 16
S ECTION 2.1 T HE B INOMIAL T HEOREM 26. The ( r + 1)th term = C x x r r r 8 8 3 4 - = C x r r r 8 8 4 4 - It is a constant term if 8 - 4 r = 0 r = 2 The constant term= C 2 8 4 2 = 448 27. The 5th term = C 10 4 x 10–4 ( - 2 y ) 4 = 3 360 x 6 y 4 28. The 7th term = C x y 6 11 11 6 6 2 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern